2020
DOI: 10.3390/life10080133
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Older Adult Disability and Primary Health Care Responsiveness in Low-Income Communities

Abstract: In Brazil and in most low- and middle-income countries (LMICs), information about how prepared the health care system is for the rapid aging of the population is scarce. We investigated the prevalence of disability and areas of life affected by disability among elders of the public primary health care in São Paulo and Manaus, Brazil. We investigated whether people with disability visited a primary care professional more frequently, the individual characteristics associated with disability, and differences by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…[45][46][47][48][49][50][51] Studies without significant results showed a trend towards either higher (n = 2) or mixed (n = 1) utilization levels among people with disabilities. 40,41,43 Coverage of key services was examined in five studies, and three found statistically significant differences by disability status among women. For example, women with disabilities had lower coverage of preventive health services such as cancer screening, gynaecological check-ups and antenatal care than those without disabilities.…”
Section: Resultsmentioning
confidence: 99%
“…[45][46][47][48][49][50][51] Studies without significant results showed a trend towards either higher (n = 2) or mixed (n = 1) utilization levels among people with disabilities. 40,41,43 Coverage of key services was examined in five studies, and three found statistically significant differences by disability status among women. For example, women with disabilities had lower coverage of preventive health services such as cancer screening, gynaecological check-ups and antenatal care than those without disabilities.…”
Section: Resultsmentioning
confidence: 99%
“…The findings demonstrated that the course of the dementia illness and its severity with the presence of comorbid neuropsychiatric symptoms can negatively affect the informal caregiver’s role and produce a lower quality of life. Montoro Pazzini Watfe et al [ 4 ] analysed the prevalence of disability and areas of life affected by disability among elders of the public primary health care in two big cities in Brazil. Both participation and mobility were the areas of life most affected by disability (ranging between 50–60% in this population).…”
mentioning
confidence: 99%